Long-term interrelations between socio-emotional and language competencies among preschool dual language learners in Germany - Ertanir, Beyhan; Kaiser-Kratzmann, Jens; Sachse, Steffi (British journal of educational psychology, 2021)
Background Recent research has shown that socio-emotional and language competencies are positively associated with each other. However, few studies have explored these associations for the second language competencies (L2) of young dual language learners (DLLs). Aims This longitudinal study investigated possible bidirectional associations between L2 language (expressive and receptive vocabulary) and socio-emotional competencies among preschool DLLs. Sample The participants were 216 German DLLs (MT1 = 52.67 months; SD = 9.54; 53% girls) who were recruited from 19 preschools. Method L2 skills were assessed at three time points over the course of one year using standardized tests for expressive and receptive vocabulary. Children’s teachers rated their socio-emotional strengths and behaviour concerns. Cross-lagged panel analyses were used to examine the temporal interplay and longitudinal directionality of effects controlling for children’s age, sex, type of language acquisition (sequential vs. simultaneous), and socio-economic status. Results Vocabulary skills and socio-emotional skills were positively correlated with one another at each time point, such that children with better language proficiency were rated by their teachers as children with higher levels of socio-emotional competence. Moreover, our results provided support for an effect of early socio-emotional skills (T1) on the relative increase in L2 vocabulary skills (T2 & T3), particularly for expressive vocabulary. However, our results did not demonstrate a statistically significant effect of better L2 language skills on the relative change in socio-emotional competencies. Conclusion Our results suggest unidirectional longitudinal relations between the socio-emotional and L2 skills, signifying the role of socio-emotional skills for the vocabulary development of DLLs.
Online veröffentlicht: 12. Dezember 2020
Gesehen am 17.11.2023